Production, characterisation and application of a recombinant ferulic acid esterase from Aspergillus tubingensis - Zwane, Eunice Nonhlanhla (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2014.